Mathématiques
abdul11
29

Développer puis réduire chaque expression. A=(5x+2) au carré + (1+3x) au carré B= (2x - 3) (2x+3) - (1+x)au carré C= (3x + 2)au carré - (2x + 3)au carré D= (4-6x) au carré + (5 - 8x) (5+8x).

+2
(1) Réponses
tutur127

bonsoir ,  A=(5x+2)² + (1+3x)² A= 25x²+20x+4+1+6x+3x² A= 28x²+26x+5 B= (2x - 3) (2x+3) - (1+x)² B= 4x²+6x-6x-9 -x²-2x-1 B=3x² -2x-10 C= (3x + 2)² - (2x + 3)² C= 9x² +12x +4 -4x² -12x -9 C=5x² - 5 D= (4-6x)² + (5 - 8x) (5+8x). D= 16 -48x +36x² +25 +40x -40x -64x² D= -28x² -48x +41

Ajouter une réponse